Blockchain Technology Challenge in the Future: : Data Security and Efficiency - Iskamto, Dedi; Juariyah, Lohana (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
The use of blockchain technology in digital data security and efficiency in the future can provide many benefits. However, this technology also has several challenges, therefore it is necessary to continue to develop blockchain technology and find ways to overcome existing challenges. Then with all the advances in blockchain technology whose existence has been felt by most people around the world, can blockchain technology provide efficiency in terms of time and cost? Does blockchain technology guarantee higher data security? Are there challenges faced by blockchain technology? What are the challenges faced by blockchain technology? How to deal with the challenges of this blockchain technology? The purpose of this writing is, It is hoped that this writing can explain about blockchain technology, the use of blockchain technology, how blockchain technology systems work, the challenges of blockchain technology, in digital data security, and the efficiency of blockchain technology in the future. So, it is hoped that this research can provide a better understanding of blockchain technology and the potential development of blockchain technology in the future. In this study, the method we will use is the Systematic Literature Review (SLR) method. It is hoped that by using this method blockchain research can get concrete or justifiable evidence so that the findings will be obtained from the results of the experts that were developed.